Entrepreneurial resilience of Gudeg msmes: Analysis of survival strategies and basic resilience factors - R. Andro Zylio Nugraha; Siti Irene Astuti Dwiningrum (Assets: Jurnal Akuntansi dan Pendidikan, 2025)
This study aims to examine the resilience of Gudeg micro, small and medium enterprises (MSMEs) in Yogyakarta with a focus on the basics of resilience and survival strategies applied by business actors. Through a qualitative approach with a case study design, data was collected through in-depth interviews, observation, and documentation of a number of Gudeg MSME owners in the Wijilan culinary center area of Yogyakarta. The results showed that the basis of MSME resilience includes two factors, namely internal and external. In both factors, there are aspects of value, appreciation, consistency, preservation, culture, innovation, activity, and product. Meanwhile, the survival strategy includes the synergy of marketing mix theory with PESTLE Analysis. The findings underscore the importance of a combination of internal and external strengths and adaptive strategies in maintaining the sustainability of traditional culinary businesses amidst changes in the business environment. This research provides practical implications for the development of MSME assistance policies based on local potential and business resilience.